2022
DOI: 10.1017/s1474746422000094
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Dimensional View of Stigma Experienced by Lone Parents in Irish Homeless and Employment Services

Abstract: This critical and empirical article explores contemporary reproduction, experience, and responses to stigma in welfare delivery in Ireland. Combining qualitative data about lone parents (n22) gathered through two different research projects in 2017 and 2018 allows us to interrogate stigma in a multi-dimensional way and as an overarching experience as an ongoing project of neo liberalism. We analyse our findings using Baumberg’s (2016) typology of stigma which differentiates claim making stigma from personal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Yet, resistance that challenges welfare ideologies does exist, even amongst those who still feel personal stigma and shame (Pemberton et al, 2016; see also Evans, 2022). Patrick (2016) found that some single mothers may challenge the view that they are getting money for no work by showing that single parenthood is, in fact, hard work (see also Finn and Murphy, 2022). Claimants also point out that fraud occurs right across different sectors of society and, in the cases for welfare fraud, is small (Patrick, 2016).…”
Section: Resisting Welfare Stigmamentioning
confidence: 99%
“…Yet, resistance that challenges welfare ideologies does exist, even amongst those who still feel personal stigma and shame (Pemberton et al, 2016; see also Evans, 2022). Patrick (2016) found that some single mothers may challenge the view that they are getting money for no work by showing that single parenthood is, in fact, hard work (see also Finn and Murphy, 2022). Claimants also point out that fraud occurs right across different sectors of society and, in the cases for welfare fraud, is small (Patrick, 2016).…”
Section: Resisting Welfare Stigmamentioning
confidence: 99%
“…The research literature on poverty highlights the impact on individuals, families, and communities of poverty, costs that are both current to the experience and reflecting its scarring effects. Beyond its direct effect on living standards, poverty has been found to force people to lead a 'marginal existence' (Whelan, 2022), stigmatise people and implicitly impacting on their selfesteem, inducing a sense of shame and powerlessness given individual's circumstances (Walker, 2014;Sutton et al, 2014;Greve, 2019a;Boland et al, 2022;Finn & Murphy, 2022). It also imposes financial stress driven by 'the relentlessness of the work involved in getting by' (Gray et al, 2019: 294).…”
Section: Introductionmentioning
confidence: 99%